A new route to an ordered array of bubbles formed during crystallization of glass. Issue 13 (September 2019) - Herrmann, Andreas; Rüssel, Christian
Abstract: A new route for the preparation of an ordered array of bubbles is presented. A glass with the mol% composition 61.4 CaO · 30.4 Al2 O3 · 8.2 SiO2 was melted, casted and then given to a muffle furnace preheated to 950 °C, which was kept for 15 h. Then the furnace was switched off. The glass crystallized from the surface, forming CaAl2 O4 and Ca3 Al2 O6, which resulted in the enrichment of water in the glass, predominantly at the crystallization front. This led to the formation of bubbles. At the other side of the bubbles, new nuclei were formed which resulted in another crystalline layer. This again led to an enrichment of water and subsequently to the formation of bubbles. Then another nucleation took place followed by another formation of a crystalline layer. In summary, alternating layers of crystals and bubble rich regions were formed and hence an ordered array of bubbles. This effect was observed for the first time.